PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DAN SELF-CONFIDENCE SISWA SMP MELALUI MODEL DISCOVERY LEARNING DENGAN PENDEKATAN PEMBELAJARAN REALISTIK - Syifa Az zahra; rahman, taufik; Vevi Hermawan; Jusep Saputra (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2024)
The purpose of this study was to analyze whether the increase in the mathematical problem solving ability of students who received the discovery learning learning model with a realistic learning approach was higher than students who received conventional learning models. The subjects in this study were students of class VIII MIPA SMPN 1 Gununghalu. The research sample used 2 classes, namely class VIII-A as the experimental class and class VIII-C as the control class. The method in this study was a quasi-experimental research design with a non-equivalent control group design. The instrument used in this research is a test description of mathematical problem solving abilities. The results showed that the increase in mathematical problem- solving skills of students who received the discovery learning model with a realistic learning approach was higher than students who received conventional learning models